THE GEO-POLITICS OF PLAN COLOMBIA - Petras, James (La Sociología en sus Escenarios, 2010)
Abstract. Plan Colombia, to be understood properly, should be located in a historical perspective both with relation to Colombia as well as in relation to the recent conflicts in Central America. Plan Colombia is both "new" policy and a continuation of past U.S. involvement in Colombia. Beginning in the early 1960s, under President Kennedy, Washington launched its counter insurgency program, forming special forces, designed to attack "internal enemies. The target was the self-defense communities in Colombia, particularly in Marquetalia and subsequently with greater or lesser intensity, the Pentagon continued its presence in Colombia. Plan Colombia thus is President Clinton’s extension and deepening of President Kennedy’s internal war the differences between the earlier version of the internal war doctrine and the current is found in the ideological justifications for U.S. intervention, the scale and scope of U.S. involvement and the regional context of the intervention. Under Kennedy counter-insurgency was based on the threat of international communism, today the justification is based on the drug threat. Resumen. Planee Colombia, para ser entendido correctamente, debe ser situado en una perspectiva histórica ambas en relación a Colombia así como en lo referente a los conflictos recientes en America Central. El plan Colombia es ambo " new" política y una continuación de la última implicación de los E.E.U.U. en Colombia. Comenzando en el principios de los 60, debajo de presidente Kennedy, Washington puso en marcha su programa contrario de la insurrección, formando las fuerzas especiales, diseñadas para atacar el " enemigos internos. La blanco era las comunidades de la autodefensa en Colombia, particularmente en Marquetalia y posteriormente con mayor o poca intensidad, el Pentagon continuó su presencia en Colombia. El plan Colombia es así presidente Clinton’ extensión de s y profundización de presidente Kennedy la guerra interna de las diferencias entre la versión anterior de la doctrina interna de la guerra y la corriente se encuentra en las justificaciones ideológicas para la intervención de los E.E.U.U., la escala y el alcance de la implicación de los E.E.U.U. y el contexto regional de la intervención. Debajo basan a Kennedy que la contraguerrilla fue basada en la amenaza del comunismo internacional, hoy la justificación en la amenaza de la droga.